STEMI in nonagenarians: Never too old. Issue 1 (12th July 2022) - Sheldon, Mark; Blankenship, James C.
Keypoints: The mortality rate of ST‐elevation myocardial infarction (STEMI) is increased in the elderly whether or not they undergo primary percutaneous coronary intervention (pPCI). If a nonagenarian presents with a STEMI, a more aggressive approach including pPCI can positively influence their chance of survival. This increased chance of survival after pPCI comes at the expense of having a modest increase in the chance of readmission to the hospital in the first 30 days.